Concerns, Perceived Impact, Preparedness in Coronavirus Disease (COVID-19) Pandemic and Health Outcomes among Italian Physicians: A Cross-Sectional Study - Igor Portoghese; Federico Meloni; Maura Galletta; Ilenia Piras; Ernesto D'Aloja; Gabriele Finco; Marcello Campagna (SAGE Publishing, 2021)
Background: Health care workers (HCWs) are among the professionals at serious risk for the impact of the COVID-19 pandemic on their mental health. In this sense, the next public health challenge globally will be to preserving healthy HCWs during this pandemic. Aim: The present study has the aim of investigating the relationship among concerns, perceived impact, preparedness for the COVID-19 pandemic and the mental health of Italian physicians. Methods: From March 29th to April 15th 2020, we conducted an online survey using snowball sampling techniques through Limesurvey platform. Data were analyzed using descriptive statistics and multiple binary logistic regressions. Results: Multivariate analysis showed that the risk factors for perceived job stress were concerns about catching COVID-19 (OR = 3.18 [95% CI = 2.00-5.05] P  < .001), perceived impact on job demands (OR = 1.63 [95% CI = 1.05-2.52] P  < .05), perceived impact on job role (OR = 2.50 [95% CI = 1.60-3.90] P  < .001), and non-working concerns (OR = 1.86 [95% CI = 1.15-3.03] P  < .05). With respect to the risk factors for rumination about the pandemic emerged concerns about catching COVID-19 (OR 1.74, [95% CI = 1.12-2.71] P  < .05), perceived impact on job role (OR = 1.68 [95% CI = 1.12-2.52] P  < .05), and impact on personal life (OR = 2.04 [95% CI = 1.08-3.86] P  < .05). Finally, the risk factors for crying at work were perceived impact on job role (OR = 2.47, [95% CI = 1.20-5.09] P  < .05), rumination about the pandemic (OR = 3.027 [95% CI = 1.27-7.19] P  < .01), watching colleagues crying at work (OR = 3.82 [95% CI = 1.88-7.77] P  < .01), and perceived job stress (OR = 3.53 [95% CI = 1.24-10.07] P  < .05). Conclusion: In general, our results highlighted that being concerned about being infected/infecting other people, carrying out new and unusual tasks, and witnessing colleagues crying at work were important risk factors for physicians' well-being. Additional data are necessary to advance understanding of these risk factors in a long-term perspective.